TRADITIONAL MARKET AND WOMEN’S WORK IN THE BERINGHARJO MARKET, OF YOGYAKARTA - Budiawati Supangkat; Rahman Latif Alfian; Johan Iskandar (Sosiohumaniora, 2021)
Traditional market is often one of the locations for economic turnover in an area. Various goods from villages, sub-districts, and other areas around the city are sent to be traded. In this market there is a large system that makes the market “live” in which there are interrelated actors. Some of the actors in the traditional market system such as the Beringharjo Market are women who work odd jobs. To see this phenomenon, this study used an ethnographic method to delve deeper into the phenomena that occur from the point of view of stakeholders in Beringharjo Market. The results of study showed that Beringharjo Market always changes from time to time, both physically and the actors who “live it”. Women who work in al kind of work become one of the actors who play an important role in the sustainability of dynamic market activities.